The woodcuts illustrating the Thesoro de la Passion by Andrés de Li (Zaragoza, 1494) and its engraved sources - Forteza Oliver, Miquela (Revista General de Información y Documentación, 2023)
This article analyzes the woodcuts that illustrate the Thesoro de la Passion by Andrés de Li. This book was printed in 1494 in Zaragoza in the printing house of Pablo Hurus. It is an extensive devotional work made up of one hundred and twenty folios that chronologically cover the most significant episodes of the public life and passion of Christ. The prints are conceived as complements to the text and their distribution is related to the demands of the text. Although some of the woodcuts are reminiscent of Martin Schongauer's Passion intaglio prints and Delbecq-Schreiber's Passion engravings, the references must have come, directly or indirectly, from different sources: from miniated manuscripts, from traditional imagery and, of course, from Central European engravings, which at this time constituted an important trade in the book trade.
Keywords: Woodcut; Engraving; Incunabula; Printing; Pablo Hurus; Passion of Christ; Martin Schongauer; Delbecq-Schreiber Passion